Peran Return On Investment dalam Upaya Peningkatan Laba pada Sektor Pariwisata Hotel - Ni Wayan Novi Budiasni (Sekolah Tinggi Ilmu Ekonomi Satya Dharma, 2021)
This study aims to determine the factors that surround Return on Investment at Holiway Garden Resort Spa Hotel. Data analysis techniques using SEM PLS method and research samples in the form of financial report data as much as 36 months. Based on the results of the hypothesis test found that, variable sales volume, operating costs, Debt Equity to Ratio, Total Asset Turnover, and cash turnover had a significant positive influence on ROI at Holiway Garden and Spa Hotel. So that all hypotheses in this study are accepted. Based on the results of the study, all these factors become important elements to be considered in financial management in order to maximize profit income in the company.